2016
DOI: 10.15441/ceem.15.096
|View full text |Cite
|
Sign up to set email alerts
|

Admission rates for emergency department patients with venous thromboembolism and estimation of the proportion of low risk pulmonary embolism patients: a US perspective

Abstract: ObjectiveIntroduction of target specific anticoagulants and recent guidelines encourage outpatient management of low risk patients with venous thromboembolism. We describe hospital admission rates over time for patients presenting to US emergency departments (EDs) with deep vein thrombosis (DVT) and pulmonary embolism (PE) and estimate the proportion of low-risk PE patients who could potentially be managed as outpatients.MethodsWe performed a structured analysis of the National Hospital Ambulatory Medical Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…8 Despite these recommendations and the increasing evidence that home treatment is safe and efficacious, many patients, even those with low risk of complications, are admitted for hospital management. 9,10 In this report, we provide a comprehensive and systematic review of the literature and elect to incorporate prospective observational studies in addition to RCTs to determine whether any evidence to avoid home management of DVT or PE exists, particularly among those with "low-risk PE. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Despite these recommendations and the increasing evidence that home treatment is safe and efficacious, many patients, even those with low risk of complications, are admitted for hospital management. 9,10 In this report, we provide a comprehensive and systematic review of the literature and elect to incorporate prospective observational studies in addition to RCTs to determine whether any evidence to avoid home management of DVT or PE exists, particularly among those with "low-risk PE. "…”
Section: Introductionmentioning
confidence: 99%
“…However, observational studies continue to report in hospital management of DVT and PE. An analysis of 652 000 and 394 000 emergency room visits in the US for DVT and PE between 2006 and 2010 indicate that 52% of DVT patients and 90% of PE patients were managed in the hospital 10. Similarly, a more recent analysis of 2387 patients diagnosed with PE across 21 emergency departments between 2013 to 2015 reports that only 7.5% of patients were managed at home 9.…”
mentioning
confidence: 99%
“…Of the approximately 900,000 annual venous thromboembolism (VTE) events occurring in the United States, it is estimated that more than 250,000 are diagnosed with pulmonary embolus in the emergency department (ED) . In a U.S. National Hospital Ambulatory Medical Care Survey analysis, during 2006 to 2010, >90% of ED patients diagnosed with pulmonary embolism (PE) were hospitalized . Since the average PE hospitalization costs approximately $14,000, this represents >$2 billion in annual expenditures.…”
Section: Importancementioning
confidence: 99%
“…More than 50% of these are in the emergency department (ED) . Historically, greater than 90% of patients with PE and most patients with DVT have been admitted to a hospital to initiate anticoagulation and to monitor for clinical deterioration . Recently, two clinical trials demonstrated the safety of outpatient treatment of patients with low‐risk PE .…”
mentioning
confidence: 99%
“…The safety and availability of direct‐acting oral anticoagulants (DOACs) may facilitate this approach . However, despite evidence supporting the outpatient treatment of DVT and PE dating back more than 20 years, the adoption of outpatient PE treatment in the United States is still limited . Clinician concerns that may limit outpatient treatment include a lack of follow‐up, unfamiliarity with the process of outpatient management, and concerns about risk stratification and associated medicolegal liability …”
mentioning
confidence: 99%